PENGGUNAAN MEDIA TEKA TEKI SILANG UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PADA MATERI BANGUN DATAR DI KELAS 3 SD - Zahroh, Fatimatus; Mariana, Neni; Muldash, Nency Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to improve mathematics learning outcomes for grade 3 elementary school students using crossword puzzle as learning media and to serve and describe how crossword puzzle media influence the learning outcome. The method used in this research is the Kemmis and Mc Taggart research method with 2 cycles. The subjects in this research were 3rd grade students at Public Elementary Schools in Surabaya with a total of 22 students. The object of this research is student learning outcomes based on working on evaluation test. This research was conducted from 7 June 2024 to 14 June 2024. Data collection techniques used interviews, observation, questionnaires and written tests. The result of the research shows that student learning outcomes Before implementing the crossword puzzle learning media, there were still 13.63% of students who fell into the good and very good categories. This figure is below the success indicator, namely 75%. After implementing the crossword puzzle learning media, the frequency of students who fell into the good and very good categories became 81.82% in the last cycle, which means there was a significant increase, namely 68.19% and this figure is above the research success indicator. Keyword: mathematic, learning media, crossword puzzle